KEANEKARAGAMAN TANAMAN PANGAN KEHUTANAN PADA LAHAN AGROFORESRTRI DI DESA HAURKUNING KECAMATAN NUSAHERANG KABUPATEN KUNINGAN - Ai Nurlaila; Ika Karyaningsih; Dian Rudiansah (Fakultas Kehutanan Universitas Winaya Mukti, 2019)
Food needs continue to increase from year to year and one of efforts in increasing food production is to cultivate forest land with potential food crops with agroforestry systems found in Haurkuning Village. The present study was conducted in March to June 2018 and aimed to determine the diversity of forestry food crops on agroforestry land and its cultivation status. This study was conducted by using interview method to every agroforestry farmer who had > 0.25 ha of land by means of random sampling. According to Regulation of Forestry Minister: 35 / Forestry Ministry-II / 2007 in Haurkuning Village there are 19 types of food crops consisting of 5 types of plants as sources of carbohydrates, 13 types of fruit-producing plants and 2 producers of fat oil, 60% of these food crops are cultivated by the society, which includes seed preparation, planting, maintenance and harvesting.